Hypocalcemia After Thyroidectomy in Patients Taking Proton Pump Inhibitors - Maxwell Rossip; F. Jeffrey Lorenz; Neerav Goyal; David Goldenberg (Laryngoscope Investigative Otolaryngology)
ABSTRACT Objective Calcium homeostasis is regulated by the effects of parathyroid hormone (PTH) and vitamin D on the bones, GI tract, and kidneys. Post‐thyroidectomy hypoparathyroidism and resultant hypocalcemia are common complications associated with prolonged hospitalization and higher costs. The long‐term use of proton pump inhibitors has been associated with metabolic disturbances, including hypocalcemia. The purpose of this study is to determine the rate of hypocalcemia following thyroidectomy in patients taking proton pump inhibitors. Materials and Methods Patients treated with total thyroidectomy between 2012 and 2022 were identified via the TriNetX Research Network. The rate of transient (0–6 months following thyroidectomy) and permanent (6–12 months following thyroidectomy) postoperative hypocalcemia was compared between patients with and without a prescription for proton pump inhibitors. Results Of 33,309 patients, 21.3% (n = 7081) took proton pump inhibitors before surgery. 50.9% and 10.76% of thyroidectomy patients taking proton pump inhibitors had hypocalcemia compared to 48.3% and 7.22% of patients without proton pump inhibitors at 0–1 and 6–12 months, respectively. Patients prescribed proton pump inhibitors had a significantly increased risk of experiencing hypocalcemia at 0–1, 1–6, and 6–12 months. Patients taking proton pump inhibitors were also at increased risk of visiting the emergency department at 1 and 6 months following surgery. Conclusions Patients taking proton pump inhibitors may be more likely to experience short‐term and permanent hypocalcemia after thyroid surgery. The current study is the largest to date, indicating an increased risk of hypocalcemia after thyroidectomy in patients taking proton pump inhibitors. Level of Evidence 3.